Scaffolding in Kindergarten Block Activities Based on Constructivism (Research and Development on Scaffolding Model for Block Activities in Kindergarten) - Jovanka, Della Raymena; Setiawan, Denny; Aisyah, Siti (Universitas Negeri Semarang, 2016)
Playing block activity aimed at developing child’s physical and motor skills in block building which come from cognitive skill which is used for thinking how to build desired building by placing some blocks horizontally and vertically. In playing block some other child’s skills will also developed. To maximize cognitive development of the children, scaffolding is needed. This activity helping children to broaden view, stimulate, and motivate children to play blocks in their best. However, the scaffolding should be in the right content and ways. For this matter, a research and development is necessary. The research is preceded by an action reserach which is aimed at looking for teachers’ best practices in giving scaffolding to children before, when, and after playing block. An outstanding kindergarten in South Tangerang, Banten Province, had been taken for the place of doing the classroom action research. As the result, the researchers together with the teachers had succesfully formulated the best way to give scaffolding to children that is by telling them a story about the building they are going to build and it is completed by giving them pictures or photos, or movies about the kind of building. However, too many angles of the building showing by the film, will make the children confuse and will reducing their quality of buildings. The last step was to tried-out this founding to another kindergarten in Bandung, West Java, and the teachers in that school were satisfied with the result.